Hubungan Antar Konsep Diri dan Minat Belajar Sejarah dengan Pemahaman Sejarah pada Siswa SMA Negeri di Boyolali Tahun 2005 - Jumadi & Sutoyo (Exsplorasi, 2006)
ABSTRACT This study is purposed to know the correlation between self-concent and the interest of historical learning with the understanding of history the towards students of State-senior High School at Boyolali. The main problem that will be solved is there any correlation between (1) self-connect and the understanding of History, (2) The interest of historical learning and the understanding of History, (3) Self consent and the interest of historical learning simuloneusly with the understanding of history. This study uses the survey method regarding on the correlative study. The sample are 331 students out of 2378 the sampling is conducted by the multi stage random sampling technique The accumulation of data uses the instruments, this is questionaire and objective test. Data analysis is conducted by regressive and correlative technique in the significant 0.05. The result of this study shows at the level of 5% is gained the significant positive correlation between (1) self-concept and the understanding of history t =6,6356; thit tab -1,64 wiyh p<0,05 rxly=0,339. (2) The interest of historical learning and the undertanding of History thit=8,363;ttab=2,64 with p<0,05rx2y=0,4187. (3) Self-concept and the interest of historical learning simultoneously with the understanding of history Fhit=43,91; Ftab=3,02 with p<0,05 and rx12=0,4593. The result regressive analysis at the significant level of 0.05 is gained (1) self-concept with the understanding of History is real with Fhit=42,7171>Ftab=3,86, (2) The interest of historical learning with the understanding of history is real with Fhit=69.9673> Ftab = 3.86. (3) Self-concept and interest of historical learning simultoneously is real with Fhit=43,9166>Ftab=3,02. The value of effective constribution of self concept is 6.966% and the interest of historical learning is 14.12%. From these contribution, it can be concluded that self-concept and the interest of historical learning can’t be neglected because it can influence the student in the understanding of History.     Key Words : Self-consept, interest of historical learning and the understanding of History.